Lawyer, jailer, ally, foe : complicity and conscience in America's World War II concentration camps - Muller, Eric L. (The University of North Carolina Press, 2023)
"In the Japanese American relocation camps of World War II, internees could, on any given day, be both clients and victims of their assigned War Relocation Authority lawyers. The morally ambiguous remit of these attorneys was wide and often contradictory, including overseeing the day-to-day administration of the camps, settling internal disputes between inmates, managing conflict between detainees and their government captors, and providing legal representation for prisoners outside of the camps. In re-creating the daily lives of these WRA attorneys, Eric L. Muller, a leading expert on Japanese American relocation and internment during World War II, seeks to capture historical subjects as three-dimensional, flawed human beings"-- Provided by publisher.